Pertanggungjawaban Hukum Merchant QRIS terhadap Kerugian Konsumen Akibat Kegagalan Settlement - Ricko Satriatama; Diky Dikrurahman (Jurnal Hukum Lex Generalis, 2026)
This study aims to analyze the legal liability of QRIS merchants for consumer losses due to settlement failures in the electronic payment system. Problems arise when a transaction is declared successful in the consumer application, but the funds are not received by the merchant within a certain period, creating legal uncertainty. The study uses a normative juridical method with a statutory and conceptual approach. Legal materials were analyzed based on the Civil Code, the Consumer Protection Law, Government Regulation Number 71 of 2019 and Bank Indonesia's QRIS regulations. The results show that the division of responsibilities between merchants and Payment System Service Providers (PJSPs) has not been clearly regulated, resulting in disharmony in norms in resolving QRIS transaction disputes. Merchants are, in principle, only responsible for the initial transaction verification stage and providing information to consumers, while responsibility for the settlement process rests with the PJSP. This study recommends strengthening regulatory harmonization and implementing the principle of joint liability to create legal certainty and consumer protection in digital payment transactions.